Exploratory study of removing nutrients from aqueous environments employing a green synthesised nano zero-valent iron. Issue 13 (7th June 2022) - Abida, Otman; Van der Graaf, Fennie; Li, Loretta Y.
ABSTRACT: This study explores the green synthesis of nano zero-valent iron (nZVI) extracted from the peel of selected waste fruits: banana (BP), mango (MP), and pomegranate (GP), for the removal of nutrients from aqueous environments. The extract was prepared by heating de-ionised water at 60°C for 5 min, adding a reducing and a stabilising agent, FeCl3, then stirring with a N2 gas flush solution to form iron nanoparticles, with a final drying step under N2 conditions. Using a variety of characterisation techniques, it was determined that nZVI particles were successfully synthesised via the reduction of iron (III) to iron (0) and stabilised by the presence of phenolic compounds in the extract. The removal of 20 mg/L nutrients from an aqueous solution carried out using the nZVIs resulted in nitrate removal of 92% (nZVI-GP), 88% (nZVI-BP), and 72% (nZVI-MP) within 5 min, whereas ∼98% phosphate was removed by all three nZVIs within 60 min. The aging effect was also tested. Aging the nZVIs for >20 days resulted in less efficient phosphate adsorption after exposure for 250 min; ∼70% phosphate removal was achieved using the nZVIs under these conditions. The mechanisms and pathways of nitrate reduction, including the adsorption of phosphate by nZVI were demonstrated, and discussed. Leachability tests of the phosphate-loaded nZVIs revealed that 10%, 28%, and 48% phosphate was released from the nZVI-GP, nZVI-BP, and nZVI-MP particles, respectively. Using waste fruit is, therefore, a viable and sustainable alternative to the traditional sodium borohydride method to produce nZVIs for environmental application. GRAPHICAL ABSTRACT: UF0001